FRI0561 The Availability of On-Demand Ultrasonography Assessment in the Most Affected Joint for Management of RA Patients in Daily Practice. (9th June 2015) - Yoshimi, R.; Takeno, M.; Toyota, Y.; Tsuchida, N.; Sugiyama, Y.; Kunishita, Y.; Kishimoto, D.; Kamiyama, R.; Minegishi, K.; Hama, M.; Kirino, Y.; Ueda, A.; et al.
Abstract : Background: Musculoskeletal ultrasonography (US) is one of the standard tools for the diagnosis and monitoring of rheumatoid arthritis (RA). Although we and other groups have proposed several sets of power Doppler (PD) US assessment procedures in arbitrary combinations of selected joints, 1-3 they do not always cover all of the affected joints. Objectives: To investigate whether US assessment in a selected joint on demand from patients is useful for monitoring RA in daily practice. Methods: PDUS was performed in 8 joints (bilateral MCP 2, MCP 3, wrist and knee joints) as the routine in a cumulative total of 406 patients with RA. At the examination, patients declared the most symptomatically affected joint. The declared joint other than the routine 8 joints was additionally scanned. PD signals were scored semiquantitatively from 0 to 3 in each joint, and total PD score-8 was calculated by summing up PD scores of the routine 8 joints. 1 Patients with positive PD signals in any joints were regarded as having active synovitis. Results: The patients were divided into three groups based on the most affected joints. Group A consisted of 209 patients having the most affected joint among the routine 8 joints, whereas 148 having the most affected joint other than the routine 8 joints were included in Group B. The remaining 49 were asymptomatic at the examination and categorized into Group C. Total PD score-8 was significantly higher in the symptomatic groups (Group A and B) than the asymptomatic group (Group C) (3.66±3.62 vs 1.08±1.56, P <0.0001). In the symptomatic groups, PD scores of the most affected joints showed high correlation with total PD score-8 ( r s =0.54, P <0.0001). For detection of active synovitis of any of the routine 8 joints, the sensitivity and specificity of assessment in the most affected joint were 67.1% and 93.5%, respectively, in the symptomatic groups, 83.5% and 100%, respectively, in Group A, and 39.4% and 88.6%, respectively, in Group B. In five patients (3.4%) of Group B, PD signals were detected in the most affected joints (shoulder, elbow, MCP 1, and 2 ankles), despite the negative results in the routine 8 joint assessments. These data suggested that US findings in the most affected joints represent those of routine 8 joint examinations well in Group A, while they provide complementary information, which is not available in the routine 8 joint examination, in Group B. Conclusions: This study suggests that on-demand US assessment in the most affected joint is practical and helpful for management of RA patients in daily practice. References: Yoshimi R, Ihata A, Kunishita Y, et al. A novel 8-joint ultrasound score is useful in daily practice for rheumatoid arthritis. Mod Rheumatol 2014; DOI:10.3109/14397595.2014.974305 (Early online). Backhaus M, Ohrndorf S, Kellner H, et al. Evaluation of a novel 7-joint ultrasound score in daily rheumatologic practice: a pilot project. Arthritis Rheum 2009;61:1194-201. Naredo E, Rodriguez M, Campos C, et al. Validity, reproducibility, and responsiveness of a twelve-joint simplified power doppler ultrasonographic assessment of joint inflammation in rheumatoid arthritis. Arthritis Rheum 2008;59:515-22. Disclosure of Interest: None declared